Phase Locked Loop-based Synchronization of Solar PV System with Single-Phase Grid for Integrated Load Supply - Kumar, Sourabh; Varghese, Albert John; Roy, Rejo; Bhattacharya, Debshree (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The integration of solar photovoltaic (PV) systems into existing electrical grids has garnered considerable attention in recent years, primarily due to its potential to enhance the utilization of renewable energy sources and mitigate greenhouse gas emissions. Incorporating solar PV systems into single-phase grids for power supply necessitates the use of efficient synchronization techniques to ensure optimal power transfer and dependable operation. Synchronizing solar PV systems with the grid offers various advantages, such as improved power quality, increased grid stability, and optimized energy utilization. The proposed concept utilizes a synchronization technique based on a Phase Locked Loop (PLL), which guarantees that the frequency and phase of the solar PV system align with those of the grid, facilitating their seamless integration. The PLL circuit extracts the fundamental frequency and phase angle from the grid voltage waveform, and then compares them with the solar PV system's output. By generating a control signal through phase and frequency adjustments, the solar PV system achieves effective synchronization with the grid, which enables efficient power transfer. A simulation model is created using MATLAB/Simulink, taking into account a single-phase grid and a solar PV system equipped with grid synchronization. The simulation results clearly illustrate the successful synchronization of the solar PV system with the grid, with minimal deviations in phase and frequency. Moreover, the integrated system can efficiently supply power to a load, ensuring uninterrupted electrical power delivery.